Internet Of Things Based Plant Watering System Design - Afu Ichsan Pradana; Harsanto; Retna Dewi Lestari; Rudi Susanto; Arif Wicaksono Septyanto (LPPM Universitas Duta Bangsa Surakarta, 2021)
The productivity of plant cultivation can be increased through intensive care and maintenance. Maintenance and maintenance consist of applying fertilizers or nutrients, weeding, pruning, and watering. Watering systems in hydroponic, aquaponic, and other plant cultivation will affect crop yields. Watering is important in maintaining lost moisture during the day, and at night as a substitute for the moisture lost at night. This study aims to design a watering tool for plant cultivation using the help of digital Internet of Things (IoT) technology. To make plant cultivation there is no lack and excess of water and nutrients. This tool can do watering remotely and can monitor moisture and soil temperature conditions via a smartphone device. Apart from helping farmers, this tool can be installed in plantations, nurseries, city parks, hotels, offices, and homes.